Detrimental Influence of Carbon Enrichment in TiO2 Nanotubes - Nasir, Amara; Mazare, Anca Valentina; Mohajernia, Shiva; Tesler, Alexander; Schmuki, Patrik; Yasin, Tariq (Proceedings of 2023 20th International Bhurban Conference on Applied Sciences and Technology, IBCAST 2023, 2023)
Carbon-modified TiO2 has been predicted as a promising candidate for a diverse range of applications such as photocatalysis, photoelectrochemistry, and energy storage and conversion. So far, the synergistic beneficial effect of carbon has been studied and reported, yet higher concentrations of carbon can produce detrimental effects such as inefficient charge separation resulting in a decreased efficiency in photo electrochemical applications. Such detrimental effects of carbon enrichment have not been investigated in detail, remaining an essential factor. This study highlights the impact of carbon enrichment on the properties and performance of TiO2 nanotubes (NTs). First, the NTs were investigated by SEM, EDX, XPS, and Raman analysis to characterize their morphology and composition. The obtained carbon-modified TiO2 NTs were used as photoelectrodes demonstrating a 2 times decrease in the IPCE efficiency compared to pristine NTs. Understanding the detrimental effect of carbon enrichment on TiO2 NT performance by advancing their synthesis and optimization strategies is vital for maximizing their efficiency in photocatalytic applications.
CRIS-Team Scopus Importer:2024-12-16
Keywords: anodization; carbon enrichment; nanotubes; photoelectrochemical; TiO2